The Impact On Mechanical Properties of Different Geometric Shapes On rHDPE Reinforcement in Concrete Structures - Kamarudin, Muhammad Hafiz (International Journal of Sustainable Construction Engineering and Technology, 2021)
This research was carried out to develop a reinforcing structure with different geometrical shapes and patterns from recycled HDPE motor oil containers to be embedded in concrete structures. The reinforcing structure was prepared by dimensioning, cutting and joining of waste HDPE. In this study, different shapes of rHDPE were used to investigate the mechanical properties of produced concrete composites based on split tensile test. Later, the fracture surface morphology of selected samples was analysed by optical microscopy (OM). The selection of optimum concrete structure was based on the interaction between different rHDPE reinforcing structure designs with the cement matrix. At the end of this study, the most suitable shapes of rHDPE were developed and proposed to be incorporated in concrete composites. This research has significant importance to provide another alternative for the construction industry that utilises the advantage of material recycling that promote more environmental friendly products and sustainable buildings.